Tanggung Jawab Notaris Terhadap Pelaksana Wasiat Yang Tidak Cakap Untuk Melaksanakan Wasiat - Natagina Putri, Riska; Yustikarini, Meliyana (UNES Law Review, 2023)
This research aims to determine the legal consequences of a will deed, one of the contents of which is the appointment of a will executor who is an incompetent person as regulated in Article 1006 of the Civil Code, as well as to determine the responsibilities of the Notary who makes the will deed and sanctions that can be imposed on a Notary who makes a will deed containing the appointment of an incompetent executor of the will. The research method used in this research is a doctrinal research method, which refers to existing legal materials, such as legal rules, legal principles, statutory regulations, legal doctrine and teachings, legal literature, and legal theories. Based on this research method, the type of research used is explanatory research, which is explanatory in nature and aims to test a hypothesis in order to strengthen the existing research hypothesis. The results of the research show that the legal consequences of a will deed appointing an incompetent executor of the will are that the deed can be null and void or a lawsuit for canceling the will can be filed in court. Apart from that, the Notary who makes it can be held civilly responsible and subject to sanctions according to the Civil Code, the Notary Position Law, and the Notary Code of Ethics.